2009
DOI: 10.1016/j.bbamcr.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cytochrome c oxidase subunit 1 is translationally downregulated in the absence of functional F1F0-ATP synthase

Abstract: The mitochondrial F1F0-ATP synthase or ATPase is a key enzyme for aerobic energy production in eukaryotic cells. Mutations in ATPase structural and assembly genes are the primary cause of severe human encephalomyopathies, frequently associated with a pleiotropic decrease in cytochrome c oxidase (COX) activity. We have studied the structural and functional constraints underlying the COX defect using Saccharomyces cerevisiae genetic and pharmacological models of ATPase deficiency. In both yeast Δatp10 and oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 66 publications
(104 reference statements)
1
37
0
Order By: Relevance
“…Much more important oxygen consumption deficits (67-85%) were observed in atp6-L252P mitochondria. A respiratory defect, especially at the level of complex IV, is a common property of yeast ATP synthase mutants [23,36]. Not surprisingly, a pronounced decrease in the content of complex IV was observed also in the mutant atp6-L252P whereas the abundance of this complex was almost normal in the atp6-S250P mutant, as revealed by BN-PAGE analysis of mitochondrial protein digitonin-extracts ( Fig.…”
Section: Mitochondrial Oxygen Consumptionmentioning
confidence: 68%
“…Much more important oxygen consumption deficits (67-85%) were observed in atp6-L252P mitochondria. A respiratory defect, especially at the level of complex IV, is a common property of yeast ATP synthase mutants [23,36]. Not surprisingly, a pronounced decrease in the content of complex IV was observed also in the mutant atp6-L252P whereas the abundance of this complex was almost normal in the atp6-S250P mutant, as revealed by BN-PAGE analysis of mitochondrial protein digitonin-extracts ( Fig.…”
Section: Mitochondrial Oxygen Consumptionmentioning
confidence: 68%
“…Because depletion of ATP synthase is known to repress translation of Cox1p and stability of Cox3p (16,53), it is not possible to distinguish between a direct and indirect effect of the gft1 mutation on these subunits.…”
Section: Discussionmentioning
confidence: 99%
“…This is highly relevant because RC complexes associate in higher order assemblies called supercomplexes or respirasomes (Schagger and Pfeiffer, 2000;Schagger and Pfeiffer 2001;Schagger, 2002;Bianchi et al, 2004;Schagger et al, 2004;Dudkina et al, 2005, Boekema andBraun, 2007;Acin-Perez et al, 2008;Dudkina et al, 2011), which have been suggested to offer structural and functional advantages to the system, such as the prevention of the destabilization and degradation of RC complexes, the enhancement of electron transport efficiency and substrate channeling, or the reduction of electron or proton leakages Koopman et al, 2010;Lenaz and Genova, 2010). As a consequence of their organization in the respirasomes, structural interdependences amongst the individual RC complexes exist (Acin-Perez et al, 2004;Schagger et al, 2004;D'Aurelio et al, 2006;Diaz et al, 2006;Li et al, 2007;Saddar et al, 2008;Soto et al, 2009;Vempati et al, 2009). This has major biological as well as biomedical implications, since structural alterations primarily affecting one given complex often induce pleiotropic deleterious effects of the other enzymes.…”
Section: Respiratory Chain Dysfunction: a Coupling Of Defective Assemmentioning
confidence: 99%